The Iraqi government operations on the Kurdistan areas in June 1963 in the Iraqi newspapers - Muneer, Rojin; Tawfiq, Hoger (Humanities Journal of University of Zakho, 2024)
‏The research period is regarded as a significant period in the history of the Aylul Revolution.The Iraqi government received assistance from several Arab and regional countries, while Britain and the United States provided weapons to target the Kurdistan region from all directions. At the same time, The Kurdish revolutionaries fought vigorously against these assaults.‏After the coup of February 8, 1963, the Iraqi newspapers played a major role in writing and publishing articles on the Kurdish issue,the views of the Iraqi government and the Kurds on the Kurdish national rights, and the Kurdish efforts to achieve them. The legitimate rights of the Kurdish people in the Iraqi national unity were also prioritized by the Iraqi newspaper engaging to find viable solutions to the Kurdish issue. ‏The newspaper was able to effectively contribute in the explanation of the incident that took place during that period, notably the intense fights that occurred between the Iraqi government and the Kurdish liberation movement.